A curriculum for life : schools for a democratic learning society - Quicke, John. (Buckingham : Open University Press, 1999)
Introduction: the curriculum and reflexive modernity. Education for self-identity. Becoming a 'good' learner. Towards a collaborative culture of professionalism. Pupils' cultural practices and collaborative group work. Teaching for cultural pluralism. Gender politics and school achievement...
Keywords: Education; Democracy; Education -- Great Britain -- Curricula; Curriculum change -- Great Britain; Democracy -- Study and teaching -- Great Britain